(untitled) (Itinera, 2023)
This issue of Itinera aims to address the connections between architecture and the performing arts in its various aspects and from multiple points of view. The growing emphasis on the performative character of artistic practices, namely, their ability to involve spectators directly and pervasively (Dixon 2007), imbues the relationship between architecture, the performing arts, and the spectator’s experience. The sharing of the scenic space by spectators and performers is essential for the co-production of a common energy which operates as a “transforming force” and thereby opens up the shared experience of discovering oneself and the other as a union of the body and the mind (Fischer-Lichte 2004).